Price trends in world agricultural trade - STEPANENKO Сергій; LARINA Тетяна; NEPRAN Андрій (Ius Modernum, 2025)
The impact of the price factor on the dynamics of foreign trade in the agricultural products of Ukraine is evaluated. The hypothesis is put forward that the price factor counteracts the increase in physical exports of agricultural products, resulting in a slowdown in the growth of revenues from foreign trade in agricultural products. It is proved that one of the key consequences of the deterioration of trade conditions was the decline in the purchasing power of exported products, which caused significant financial losses for producers. In particular, in recent years, there has been a steady downward trend in world prices for the main types of Ukrainian agricultural products, which is one of the determining factors in the deterioration of trade conditions. The quantitative assessment of the impact of changes in the structure and dynamics of trade on agricultural sector revenues showed that in 2023 the total losses from unfavourable terms of trade amounted to USD 4.4 billion, including USD 2.9 billion in grain exports alone. Based on the factor analysis, it was found that even the increase in physical export volumes could not compensate for the losses of trade income caused by the decline in prices. Moreover, the results of the study of the trade balance of agricultural products show that export growth is accompanied by an even more rapid increase in imports, which leads to a deterioration in the overall dynamics of the industry’s foreign trade balance. The study results call into question the effectiveness of the state strategy focused on increasing physical exports as the main mechanism for developing the agricultural sector. This approach does not take into account the need to increase the added value of products and diversify markets, which is critical in the face of increasing global competition. Instead, the sector’s development strategy should include stimulating the production of high-tech products, expansion of the processing industry, and the formation of effective mechanisms to protect domestic producers in foreign markets. Thus, the study confirms the need to rethink approaches to the formation of Ukraine’s foreign economic policy in the field of agricultural exports, which should be based not only on a quantitative increase in supply but also on qualitative changes in the structure of production and trade.